Electrical engineering reviewer (Quezon City, Philippines : Technical Publications, 1974)
Part one among the series of reviewers for those who are planning to take their licensure's exam.
Chapter1. Linear circuits -- Chapter2. Transformer -- Chapter3. The national electrical code -- Chapter4. Machinery -- Chapter5. Power transmission and distribution -- Chapter6. Illumination -- Chapter7. Wire communication -- Chapter8. Electronic circuits -- Chapter9. Wave analysis -- Chapter10. Transient -- Chapter11. The electrical circuit analog -- Chapter12. Miscellaneous problems .
Includes bibliographical references and index.